Changing China through a dialogue between Science and Faith: Ferdinand Verbiest (1623-1688) and the “cold plum standing alone in the snow” (The Macau Ricci Institute Journal, 2023)
On 9 October 2023 in Beijing we celebrated the 400th birthday of Ferdinand Verbiest who is considered one of the most outstanding missionaries in China following in the footsteps ofMatteo Ricci and Johann Adam Schall von Bell.The Symposium on “Exploring the Mysteries of Heaven with Ferdinand Verbiest: Dialogue between Science and Faith” provided an opportunity for the Macau Ricci Institute at the University of St. Joseph to cooperate with the Embassy of Belgium in China, the Yale Center Beijing, the Korean Center for Innovation and the Swiss Chamber of Commerce. This overview of the extremely rich encounter limits itself to briefly highlightingthree core dimensions of our combined effort which was in line with the last fourth centenary celebration in 2010 recalling the death of Matteo Ricci 400 years ago. From a Western pointof view, it may not easily be understandable how much the memory of friends is greatly valued and appreciated in China over the span of several centuries.While it was encouraging to see how many people on different levels of society in Belgium did enthusiastically join this event on a stunningly beautiful autumn day in Beijing–which includeda visit to the six Astronomical instruments at the Ancient Observatory in downtown Beijing–should not let us ignore the fact that Ferdinand Verbiest like other luminaries did a long time ago fall into oblivion in Europe.